Target position reproducibility in left‐breast irradiation with deep inspiration breath‐hold using multiple optical surface control points. (8th May 2018) - Fassi, Aurora; Ivaldi, Giovanni B.; de Fatis, Paola Tabarelli; Liotta, Marco; Meaglia, Ilaria; Porcu, Patrizia; Regolo, Lea; Riboldi, Marco; Baroni, Guido
Abstract: The aim of this study was to investigate the use of 3D optical localization of multiple surface control points for deep inspiration breath‐hold (DIBH) guidance in left‐breast radiotherapy treatments. Ten left‐breast cancer patients underwent whole‐breast DIBH radiotherapy controlled by the Real‐time Position Management (RPM) system. The reproducibility of the tumor bed (i.e., target) was assessed by the position of implanted clips, acquired through in‐room kV imaging. Six to eight passive fiducials were positioned on the patients' thoraco‐abdominal surface and localized intrafractionally by means of an infrared 3D optical tracking system. The point‐based registration between treatment and planning fiducials coordinates was applied to estimate the interfraction variations in patients' breathing baseline and to improve target reproducibility. The RPM‐based DIBH control resulted in a 3D error in target reproducibility of 5.8 ± 3.4 mm (median value ± interquartile range) across all patients. The reproducibility errors proved correlated with the interfraction baseline variations, which reached 7.7 mm for the single patient. The contribution of surface fiducials registration allowed a statistically significant reduction ( p  < 0.05) in target localization errors, measuring 3.4 ± 1.7 mm in 3D. The 3D optical monitoring of multiple surface control points may help to optimize the use of the RPM system for improving target reproducibility in left‐breast DIBH irradiation, providing insights on breathing baseline variations and increasing the robustness of external surrogates for DIBH guidance.